PENANGANAN PERTAMA CEDERA OLAHRAGA MENGGUNAKAN METODE RICE PADA KLUB BELADIRI KARATE DOJO QOLBU - Herlina, Herlina; Burhan, Zakir; Ashari, Lalu Hasan (Devote: Jurnal Pengabdian Masyarakat Global, 2023)
This community service aims to provide understanding and an overview to the wider community about the right steps, especially for the first treatment of sports injuries with the RICE method. The RICE method is one of the injury management methods that aims to prevent further injury and reduce pain. The purpose of this community service is to provide scientific knowledge in the field of handling sports injuries with the RICE method. The problems faced by the trainer in the implementation of this Community training Program that are not yet known by the trainer's application or use of the RICE method when a player is injured and also his lack of knowledge about what types of injuries can be directly treated with the RICE method. the benefits of the exercises taught The implementation of community service activities regarding the first handling of injuries using the RICE method carried out has been running well and smoothly. trainers who are karate martial arts athletes feel the direct benefits of the exercises taught. From the interviews conducted, the trainers felt that it was very important for sports players to do this. due to the lack of knowledge about the first handling of wounds using the RICE method which is very useful for minimizing the occurrence of serious injuries and recurrence of injuries if not handled properly.